PREVALENCIA DE CARIES Y GINGIVITIS EN PREESCOLARES - Franco C, Angela María (CES Odontología, 2011)
En el presente estudio se describe el estado de salud bucal de 364 niños preescolares (1-5 años) matriculados en los Hogares Infantiles del Instituto Colombiano de Bienestar Familiar de la ciudad de Medellín. Se encontró una prevalencia de caries del 45%, con diferencias importantes según la edad y el sexo de los niños. Las oportunidades de atención odontológica, medidas a través del índice de dientes obturados, son pocas. ya que se encontró una razón de un diente obturado por cada 4 dientes cariados. La severidad de la caries dental es considerablemente menor que la que reportan estudios, pues el índice de extracción indicada sólo fue del 0.02. Todo lo anterior se resume en un índice ceo de 2 para la población estudiada. La placa dental y la gingivitis tienen alta prevalencia (95.6% y 71.7%, respectivamente); sin embargo, los índices calculados permitieron establecer que la gran mayoría de los niños presentan grados leves de acumulación de placa y de inflamación gingival. Estos hallazgos sustentan la necesidad de programas continuos de promoción, prevención y atención desde edades muy tempranas. ABSTRACT Maternal and child groups have been reported to have priority in the establishment of health prevention and assistance programs according to different organisms which dictate health policies. However, in order to satisfactorily answer their needs, clarity must be established as to the epiderniological profile of these population groups and therefore determine the most frequent diseases and risk factors which affect them. This study describes the oral health status of 364 preschool children (1-5 years oid) enrolled in the Children-Care Centers of the Colombian Family Welfare Institute in Medellin, Colombia. A caries prevalence of 45% was found with important differences between age and sex. The access to dental care, measured by means of the filled teeth index, was low, given that there was a ratio of 1 filled tooth per 4 teeth with carious lesions. Severity of carious lesions was considerably Iower when compared with other studies, since the index of indicated extractions was only 0.02. In summary, there was a dfm index of 2 for the population studied. There was a high prevalence of dental plaque (95.6%) and gingivitis (71.7%). However, the calculated indexes revealed that the majority of children presented mild degrees of plaque accumulation and gingival inflammation. These findings support the need for continuos promotion, prevention and assitance programs for children at a very early age.